Development of Teaching Factory Learning Model in Industrial Automation in Vocational High Schools - Hatmojo, Yuwono Indro; Ikhsannudin, Wahyu (DPTE FT UNY, 2024)
Vocational High Schools, as schools that aim to prepare students for work in a particular field, need effectiveness in the learning process. Its effectiveness must follow the real conditions required by the industry. With the rapid devel-opment of industry, industry-based learning, often called